Household Waste Management Strategy in Upper Middle Housing - Utama, Susan Rendra; Ahyanti, Mei (Jurnal Kesehatan, 2023)
The growing volume of waste poses a significant challenge, with implications for environmental contamination, health, and aesthetics. While participatory waste management practices have been adopted in some areas, others resort to dumping on vacant land, leading to potential long-term repercussions. The focus on waste source management, particularly within households, becomes imperative. A descriptive study was conducted in the Sukabumi Sub-district, with the most residences. Targeting households with heads of families as respondents, the research encompassed a sample of 120 housing units selected through systematic random sampling. Instruments developed by the researcher were employed for data collection. Analysis was anchored on a univariate approach and the SWOT (Strengths, Weaknesses, Opportunities, Threats) method. The community's education, knowledge, and occupation profiles were categorized as 'good'. Despite this, a gap in waste governance was identified. Community knowledge about waste management emerged as a strength, while the unrealized potential of converting organic household waste into compost was recognized as an opportunity. To address waste management effectively, it is recommended to prioritize community strengths and harness available opportunities, like independent composting through suitable technology for limited land areas. Emphasizing household waste reduction through the 3R+P model, tailored for upper-middle-class housing, and bolstering community waste management awareness through continuous campaigns is essential.